Room temperature ferromagnetism in undoped and Fe doped ZnO nanorods: microwave-assisted synthesis - Limaye, Mukta V.; Singh, Shashi B.; Das, Raja; Poddar, Pankaj; Kulkarni, Sulabha K. (Journal of Solid State Chemistry, 2011)
One-dimensional (1D) undoped and Fe doped ZnO nanorods of average length similar to 1 mu m and diameter similar to 50 nm have been obtained using a microwave-assisted synthesis. The magnetization (M) and coercivity (H-c) value obtained for undoped ZnO nanorods at room temperature is similar to 5 X 10(-3) emu/g and similar to 150 Oe, respectively. The Fe doped ZnO samples show significant changes in M -H loop with increasing doping concentration. Both undoped and Fe doped ZnO nanorods exhibit a Curie transition temperature (T-c) above 390 K. Electron spin resonance and Mossbauer spectra indicate the presence of ferric ions. The origin of ferromagnetism in undoped ZnO nanorods is attributed to localized electron spin moments resulting from surface defects/vacancies, where as in Fe doped samples is explained by F center exchange mechanism. (C) 2010 Published by Elsevier Inc.
Keywords: Diluted magnetic semiconductors; Nanostructures; ZnO